Kajian potensi limbah tulang sirip Ikan Tuna (Thunnus Sp) sebagai sumber gelatin dan analisis karakteristiknya - Dahlia Dahlia; Rahman Karnila; Yusni Ikhwan Siregar (Pelantar Press, 2018)
Gelatin is a protein from the hydrolysis of bone collagen and skin of animals wich are widely used for industrial food and non food. Studies on extraction of gelatin from tuna (Thunnus sp) bone were carried out by soaking in hydrochloric acid solutions of 4%, 6% and 8% for 48 hours respectivelly and extracted with aquadest at 60ºC, 70ºC and 80ºC for 5 hours. The extract was filtered with filtering cloth and the filtrate was oven dried at 55ºC for ± 48 hours until gelatin was formed. The result showed that soaking the bone in 8% hydrochloric acid solutions followed by extraction 80ºC for 5 hours gave the best result with 8,64 yield, isoelectrict point 8,20%, protein contain 93,72%, lipid contain 0,74-1,75%. Gel strengh 257,59 g/bloom gel strengh, viscosity 3,20 cPs, pH 3,98. The results obtained for water contain of 6,97%. Ash countain 2,07%. The colour of gelatin produced from tuna bone showered different with commercial gelatin that is between yellowish brown to whitish yellow. Gelatin made from tuna bone has fishy odor whereas commercial gelatin has neutral odor.